TAMI-11. IMPACT OF oHSV ACTIVATED NOTCH SIGNALING IN TUMOR MICROENVIRONMENT, AND ITS IMPACT ON ANTI-TUMOR IMMUNITY. (9th November 2020) - Otani, Yoshihiro; Yoo, Ji Young; Chao, Samantha; Shimizu, Toshihiko; Lewis, Cole; Murphy, Sara; Pineda, Josue; Caraballo, Kimberly Rivera; Hong, Bangxing; Banasavadi-Siddegowda, Yeshavanth Kumar; Heiss, John; Yan, Yuanqing; et al.
Abstract: NOTCH signaling is a method of cell-cell communication where membrane bound NOTCH ligands on signal-sending cells can bind to and initiate cleavage of the NOTCH receptor, releasing NICD which can initiate signal transduction in adjacent "signal-receiving" cells. We have recently shown that oHSV treatment of GBM cells induces NICD cleavage and NOTCH activation in adjacent uninfected glioma cells. RNA sequencing of GBM cells post-infection also uncovered Gene Ontology NOTCH signaling pathway to be significantly upregulated. This activation was induced by viral miRNA-H16, which represses FIH-1 expression. FIH-1 was found to be a negative regulator of Mib1, a ubiquitin ligase, which activates NOTCH ligand-mediated activation of adjacent signal-receiving cells bearing the NOTCH receptor (Otani et al Clin. Can. Res. 2020). Here we have investigated the impact of oHSV-induced NOTCH signaling on the tumor microenvironment. Treatment of brain tumors in immune competent mice with oHSV and NOTCH blocking gamma secretase inhibitor (GSI) induced an anti-tumor memory immune response. Long term survivors in mice treated with the combination also completely rejected subsequent tumor re-challenge in the other hemisphere. UMAP of flow cytometry of tumor-bearing hemispheres and functional analysis of isolated cellular fractions from treated mice showed a significant influx of MDSC cells after oHSV treatment that was rescued in mice treated with oHSV and GSI. Ongoing mechanistic studies are uncovering a significant induction of NOTCH in tumor associated macrophages that aids in recruitment of MDSC cells. Overall these studies have uncovered a significant impact of oHSV therapy on GBM tumor microenvironment and presents opportunities for combination therapies that can help improve therapeutic benefit and anti-tumor immunity.